EFEKTIVITAS TERAPI RELAKSASI OTOT PROGRESIF DALAM MENURUNKAN HIPERTENSI PADA LANSIA - M Ilham; Armina Armina; Hasyim Kadri (Jurnal Akademika Baiturrahim Jambi, 2019)
The prevalence of cases of hypertension is very high in the elderly, namely 60% -80% at the age above 65 years. The number of elderly people suffering from hypertension at Budi Luhur Jambi PSTW in November 2018 was 22 elderly and had received regular hypertension medication every day but the elderly blood pressure was still high. The purpose of this study is to see whether there is any effect of progressive muscle relaxation therapy on blood pressure in elderly people with hypertension. This study used the Quasi Experiment method with the design of Non Equivalent Control Group Pretest-Posttest, with random sampling technique, the number of samples was 20 elderly consisting of 10 elderly experimental groups given hypertension drugs as well as progressive muscle relaxation therapy and 10 elderly control groups who only given hypertension medication. This research was conducted at Budi Luhur PSTW Jambi on 28 January-2 February 2019. Progressive muscle relaxation therapy is given once a day every morning for six consecutive days. Based on the analysis using the Dependent T test in the experimental group, it was found that systolic blood pressure was p value 0.0001 and diastolic blood pressure was p value 0.002 <(0.05). the results of the analysis using the Independent T test found differences in the blood pressure of the experimental group and control where systolic blood pressure p value 0.031 <(0.05), while the diastolic blood pressure p value 0.009 <(0.05), it can be concluded that there significant to the blood pressure of elderly people with hypertension before and after being given progressive muscle relaxation therapy. This study is expected to be a new program at PSTW Budi Luhur Jambi to reduce high blood pressure in elderly people who suffer from hypertension.